Effect of Eicosapentaenoic Acid on E-type Prostaglandin Synthesis and EP4 Receptor Signaling Human Colorectal Cancer Cells - Hawcroft, Gillian; Loadman, Paul M.; Belluzzi, Andrea; Hull, Mark A. (Neoplasia (New York, N.Y.), 2010)
The ω-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA), in the free fatty acid (FFA) form, has been demonstrated to reduce adenoma number and size in patients with familial adenomatous polyposis. However, the mechanistic basis of the antineoplastic activity of EPA in the colorectum remains unclear. We tested the hypothesis that EPAFFA negatively modulates synthesis of and signaling by prostaglandin (PG) E2 in human colorectal cancer (CRC) cells. EPA-FFA induced apoptosis of cyclooxygenase (COX)-2-positive human HCA-7 CRC cells in vitro. EPA-FFA in cell culture medium was incorporated rapidly into phospholipid membranes of HCA-7 human CRC cells and acted as a substrate for COX-2, leading to reduced synthesis of PGE2 and generation of PGE3. Alone, PGE3 bound and activated the PGE2 EP4 receptor but with reduced affinity and efficacy compared with its “natural” ligand PGE2. However, in the presence of PGE2, PGE3 acted as an antagonist of EP4 receptor-dependent 3’,5’ cyclic adenosine monophosphate induction in naturally EP4 receptor-positive LoVo human CRC cells and of resistance to apoptosis in HT-29-EP4 human CRC cells overexpressing the EP4 receptor. We conclude that EPA-FFA drives a COX-2dependent “PGE2-to-PGE3 switch” in human CRC cells and that PGE3 acts as a partial agonistat the PGE2 EP4 receptor.